Peran Fintech dalam Pembentukan Pasar Global untuk Mata Uang Digital: Dampak Terhadap Stabilitas Ekonomi - Nur Rohmah, Nelly; Najibah, Nu’matun; Rohmawati, Amelia; Lela Saputri, Pungky (PENG: Jurnal Ekonomi dan Manajemen, 2025)
The development of information and communication technology has driven significant innovation in the financial sector through Financial Technology (Fintech). This article explores the role of Fintech in shaping the global market for digital currencies and its impact on economic stability. Using a qualitative descriptive approach and literature review, this study finds that Fintech, through technologies such as blockchain, peer-to-peer (P2P) lending, and Decentralized Finance (DeFi), facilitates efficient cross-border transactions, enhances financial inclusion, and creates a more interconnected global financial ecosystem. Additionally, digital currencies such as cryptocurrencies and Central Bank Digital Currencies (CBDCs) offer potential benefits in transaction efficiency, transparency, and reduced global transaction costs. However, the adoption of digital currencies also presents challenges, including high value volatility, risks to monetary policy, and opportunities for illegal activities such as money laundering. This article recommends the importance of comprehensive global regulatory policies to mitigate risks, control the circulation of digital currencies, and ensure economic stability in the digital era. Thus, Fintech and digital currencies can be optimized as catalysts for supporting inclusive and sustainable global economic growth.